Safety for the user of the feed additive consisting of ferric citrate chelate (CI‐FER™) for suckling and weaned piglets and minor porcine species (Akeso Biomedical, Inc.) - Bampidis, Vasileios (EFSA J, 2021)
Following a request from the European Commission (EC), the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) was asked to deliver a scientific opinion on the safety for the users of the feed additive consisting of ferric citrate chelate (CI‐FER™) when used as a zootechnical additive for suckling and weaned piglets and minor porcine species. The EC request follows a previous opinion of the FEEDAP Panel. In that opinion, the Panel identified several risks for the users of the additive; it was listed that it posed a risk to users by inhalation, should be considered as an irritant to skin, eyes and mucous membranes, and also that, due to its nickel content, should be considered as a dermal and respiratory sensitiser. The applicant provided additional data including information on the manufacturing process of the additive and data supporting the safety of the additive for the users to address those concerns. Some changes have been applied to the original manufacturing process which led to a dust‐free additive, with the following specifications: total iron ≤ 23%, iron (III) ≥ 16.5% and moisture ≤ 10.0%. The FEEDAP Panel concluded that CI‐FER™ does not pose a risk by inhalation and is classified as non‐irritant to the skin. The additive should be classified as a skin sensitiser. In the absence of new data, the FEEDAP Panel reiterates its previous conclusion that the additive should be considered irritant to eyes.